2017
DOI: 10.5539/jedp.v7n2p43
|View full text |Cite
|
Sign up to set email alerts
|

Does the Number of Available Strategies Change How Children Perform Cognitive Tasks? Insights from Arithmetic

Abstract: Fifth and seventh-graders accomplished computational estimation tasks in conditions where only one versus two strategies were available. Children were told which strategy to execute on each problem. Results showed that both groups of children were faster under one-strategy condition than under two-strategy condition and that age-related differences in performance were larger under two-strategy condition. Also, differences in strategy performance tended to vary as a function of the number of strategies, and thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…In other words, being able to choose among finger-based and non-finger strategies helped children's performance of all age groups, either on accuracy (younger children) or on latency (older children). This result has been found in numerous previous arithmetic studies in children of different age groups, with different sets of available strategies for different arithmetic operations and tasks (e.g., Lemaire et al, 2017;Lemaire & Brun, 2016;Lemaire & Callies, 2009;Luwel et al, 2005). Like in previous studies, the choice benefits found here are the result of children's being able to select each strategy when it works best (i.e., when it yields either more accurate or faster performance, or both) on each problem.…”
Section: Discussionsupporting
confidence: 83%
“…In other words, being able to choose among finger-based and non-finger strategies helped children's performance of all age groups, either on accuracy (younger children) or on latency (older children). This result has been found in numerous previous arithmetic studies in children of different age groups, with different sets of available strategies for different arithmetic operations and tasks (e.g., Lemaire et al, 2017;Lemaire & Brun, 2016;Lemaire & Callies, 2009;Luwel et al, 2005). Like in previous studies, the choice benefits found here are the result of children's being able to select each strategy when it works best (i.e., when it yields either more accurate or faster performance, or both) on each problem.…”
Section: Discussionsupporting
confidence: 83%
“…Switch costs, or deficits in response time or accuracy, occur when switching from one familiar strategy to another (Brass, Derrfuss, & von Cramon, 2007). They are thought to arise from the shift in neural activity associated with how each strategy guides behavior (Lemaire, Luwel, & Brun, 2017; Luwel et al, 2009; Meiran, 1996). Both human children and adults exhibit switch costs on trials that require them to switch from one familiar strategy to another (Arrington & Logan, 2004; Ionescu, 2012; Rogers & Monsell, 1995; Zelazo, 2008), even after extensive practice (Stoet & Snyder, 2008).…”
mentioning
confidence: 99%
“…Similarly, cued-switch tasks assess subjects’ ability to shift between known strategies by comparing trials that require subjects to either repeat their previous strategy ( stay trials) or switch to another strategy ( switch trials) within their repertoire (Stoet & Snyder, 2008; Zelazo, 2008). Indeed, on cued-switch tasks, both children and adults exhibit pronounced deficits in response time and/or accuracy on switch compared with stay trials (Diamond & Kirkham, 2005; Ionescu, 2012; Lemaire, Luwel, & Brun, 2017; Luwel, Schillemans, Onghena, & Verschaffel, 2009; Stoet & Snyder, 2008). Termed “switch costs,” these deficits are thought to be associated with disengaging from one strategy and initiating another (Meiran, 1996; Rogers & Monsell, 1995; Stoet & Snyder, 2007); however, they are not exhibited by some nonhuman primates ( Macaca mulatta ; Stoet & Snyder, 2003, 2008), suggesting that they may be a byproduct of human rule-encoding (however, see Caselli & Chelazzi, 2011).…”
mentioning
confidence: 99%